2017
DOI: 10.1016/j.hrthm.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Device pacing diagnostics overestimate effective cardiac resynchronization therapy pacing results of the hOLter for Efficacy analysis of CRT (OLÉ CRT) study

Abstract: Current device pacing diagnostics overestimate the amount of CRT pacing actually delivered. The new algorithm quantifies ineffective CRT pacing, which enables clinicians to identify patients with this issue and to address the reasons behind suboptimal CRT delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The important endpoint of true LV capture can only be monitored by devices with LV sensing or—to a certain extent—by dedicated device algorithms (EffectivCRT™, Medtronic, MN) 15 . A missed insufficient LV pacing rate may be responsible for nonresponse to CRT 7,8 . The predominant reason for LV pacing interrupts was intermittent loss of LV capture in more than 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The important endpoint of true LV capture can only be monitored by devices with LV sensing or—to a certain extent—by dedicated device algorithms (EffectivCRT™, Medtronic, MN) 15 . A missed insufficient LV pacing rate may be responsible for nonresponse to CRT 7,8 . The predominant reason for LV pacing interrupts was intermittent loss of LV capture in more than 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring allows for the identification of suboptimal LV pacing percentage but the cause often remains unclear and can be challenging to counteract. Moreover, even if very high resynchronization rates are obtained according to the CRT device, the true LV capture rate is an overestimation, which has been shown in long‐term electrocardiography studies 7,8 . The true LV capture rate can be difficult to judge without an LV electrogram (EGM) 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 When applied to a general CRT patient population in an observational study (N 5 57), the diagnostic demonstrated that %Vp overestimated %eCRT pacing by an average of 7.3% 6 22.2% (P ,.05). 6 A novel algorithm has been developed that increases the amount of effective CRT delivered during AF (eCRTAF). Using the %eCRT diagnostic, it monitors beat-to-beat LV capture during AF and adjusts pacing rate to maximize %eCRT pacing while minimizing any increase in pacing rate.…”
Section: Introductionmentioning
confidence: 99%